2018
DOI: 10.1002/jmri.26249
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Kurtosis at 3.0T as an in vivo Imaging Marker for Breast Cancer Characterization: Correlation With Prognostic Factors

Abstract: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 41 publications
(82 reference statements)
7
56
3
Order By: Relevance
“…D-value reflects the diffusion dynamics of water molecule, which may be limited in the crowded tumor cellularity with a high proliferative activity. Increased Ki-67 expression suggested higher cellularity and active vascular hyperplasia (25). In this study, D-value revealed negative and moderate correlations with tumor volume (r = −0.662) and Ki-67 (r = −0.781), indicating D-value can be used to predict treatment efficacy.…”
Section: Discussionmentioning
confidence: 54%
“…D-value reflects the diffusion dynamics of water molecule, which may be limited in the crowded tumor cellularity with a high proliferative activity. Increased Ki-67 expression suggested higher cellularity and active vascular hyperplasia (25). In this study, D-value revealed negative and moderate correlations with tumor volume (r = −0.662) and Ki-67 (r = −0.781), indicating D-value can be used to predict treatment efficacy.…”
Section: Discussionmentioning
confidence: 54%
“…Jensen et al (11) first introduced the DKI model in 2005 and developed new fields in brain, liver, and prostate imaging afterward (12)(13)(14). The investigation of breast tumors using the DKI model reached a peak in 2019 and became an important research area thereafter (8,(15)(16)(17)(18)(19)(20). The model provides microscopic information regarding the deviation of water diffusion from Gaussian distribution with the mean kurtosis (MK) and mean diffusivity (MD), a kurtosiscorrected diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…DKI and DWI data were analyzed using an in-house program written in MATLAB (version R2013b, MathWorks, MA, USA). The DKI parameter was fitted according to the following equation [10][11][12][13]:…”
Section: Imaging Analysismentioning
confidence: 99%
“…The ADC is the mean value obtained using all b values that were fitted with a conventional mono-exponential model according to the following equation [11,12]:…”
Section: Imaging Analysismentioning
confidence: 99%
See 1 more Smart Citation